2011
DOI: 10.2319/032911-226.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hawley retainers on consonants and formant frequencies of vowels

Abstract: Objective: To assess (1) whether Hawley retainers cause speech disturbance and (2) the duration of speech adaptation to Hawley retainers with objective and subjective tests. Materials and Methods: Twelve adolescents, aged 11.11 to 18.03 years, were included in this study. The assessment of speech sounds were done subjectively using an articulation test and objectively using acoustic analysis before and after Hawley retainer application. Results: After wearing Hawley retainers, patients showed statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…Kayıkcı et al 17 used Hawley retainers and found statistically significant speech disturbances in consonants [s ] and [z]. In addition, the authors found that the F 1 frequency of the vowel /i/ increased, whereas F 2 and F 3 decreased.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kayıkcı et al 17 used Hawley retainers and found statistically significant speech disturbances in consonants [s ] and [z]. In addition, the authors found that the F 1 frequency of the vowel /i/ increased, whereas F 2 and F 3 decreased.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the /a/ vowel serves as the phonological core of many syllables. 9,16,17 Thus, we have examined the parameters of the /a/ vocal in evaluating the voice.…”
Section: Methodsmentioning
confidence: 99%
“…Majority population in Malaysia is Malay (60%) and the national language was Bahasa Malaysia [13]. In this study, the consonant sounds of /t d k n s/ were analyzed as these phonemes were the most likely to have distortion of speech in patients according to literature review done [7][8][9][10]. Furthermore, analysis was limited to the consonants because these sounds are much less affected by differences in dialect [14].…”
Section: Discussionmentioning
confidence: 99%
“…The design is Adam's clasps with 0.7 mm diameter stainless steel wire on the first molars and a labial bow with 0.7mm diameter stainless steel wire which span from canine to canine (Figure 1). The acrylic part (Impact Orthodontic Resin) was kept at a uniform thickness of 2 to 3mm on the palatal for each retainer, as suggested by Kulak Kayikci et al [10]. All retainers were constructed by a single technician.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation